Corporate governance of a multinational enterprise: Firm, industry and institutional perspectives - Filatotchev, Igor; Poulsen, Annette; Bell, R. Greg (Journal of Corporate Finance, 2019)
We introduce the topic of this Special Issue of the Journal of Corporate Finance on corporate governance of a multinational enterprise with a particular emphasis on the theoretical and empirical gaps in prior finance and international business studies associated with corporate governance problems and the effectiveness of governance solutions in the context of diverse institutional settings. We integrate analysis of the accepted articles with existing research on international corporate governance and global strategy. Overall, the work in this area continues to emphasize the importance of institutions, legal environment and culture in all aspects of global enterprises. We conclude the article with suggestions for future research in this rapidly expanding and important area of global business.